Analysis of in vitro and in vivo metabolism of zidovudine and gemfibrozil in trans‐chromosomic mouse line expressing human UGT2 enzymes. Issue 6 (24th November 2022) - Kobayashi, Kaoru; Deguchi, Tsuneo; Abe, Satoshi; Kajitani, Naoyo; Kazuki, Kanako; Takehara, Shoko; Nakamura, Kazuomi; Kurihara, Atsushi; Oshimura, Mitsuo; Kazuki, Yasuhiro
Abstract: UDP‐glucuronosyltransferases (UGTs) catalyze the conjugation of various substrates with sugars. Since the UGT2 family forms a large cluster spanning 1.5 Mb, transgenic mouse lines carrying the entire human UGT2 family have not been constructed because of limitations in conventional cloning techniques. Therefore, we made a humanized mouse model for UGT2 by chromosome engineering technologies. The results showed that six UGT2 isoforms examined were expressed in the liver of adult humanized UGT2 (hUGT2) mice. Thus, the functions of human UGT2B7 in the liver of hUGT2 mice were evaluated. Glucuronide of azidothymidine (AZT, zidovudine), a typical UGT2B7 substrate, was formed in the liver microsomes of hUGT2 mice but not in the liver microsomes of wild‐type and Ugt2‐knockout mice. When AZT was intravenously administered, AZT glucuronide was detected in the bile and urine of hUGT2 mice, but it was not detected in the bile and urine of wild‐type and Ugt2‐knockout mice. These results indicated that the hUGT2 mice express functional human UGT2B7 in the liver. This finding was also confirmed by using gemfibrozil as an alternative UGT2B7 substrate. Gemfibrozil glucuronide was formed in the liver microsomes of hUGT2 mice and was mainly excreted in the bile of hUGT2 mice after intravenous dosing of gemfibrozil. This hUGT2 mouse model will enable improved predictions of pharmacokinetics, urinary and biliary excretion and drug–drug interactions mediated by human UGT2, at least UGT2B7, in drug development research and basic research. Abstract : Generation of a fully humanized mouse for UGT2 (hUGT2 mouse). Transchromosomic (Tc) mice carrying the MAC with the human UGT2 cluster (UGT2‐MAC) were mated with Ugt2‐KO mice to generate hUGT2 mice.